2001
DOI: 10.1021/es0016654
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Diesel Engine Nanoparticles Using a Nano-DMA/Thermal Desorption Particle Beam Mass Spectrometer

Abstract: Diesel engines are known to emit high number concentrations of nanoparticles (diameter < 50 nm), but the physical and chemical mechanisms by which they form are not understood. Information on chemical composition is lacking because the small size, low mass concentration, and potential for contamination of samples obtained by standard techniques make nanoparticles difficult to analyze. A nano-differential mobility analyzer was used to size-select nanoparticles (mass median diameter approximately 25-60 nm) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
215
2
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(246 citation statements)
references
References 55 publications
26
215
2
3
Order By: Relevance
“…The diesel exhaust spectrum was compared to laboratory generated diesel fuel and lubricating oil spectra and the study concluded that under most operating conditions the organic carbon fraction of in-use diesel vehicle exhaust aerosol is dominated by the recondensed vapour from the evaporated engine lubricating oil. These findings were similar to those found by Tobias et al (2001), which concluded that the dominant organic components of fuel and lubricating oil are n-alkanes, branched alkanes, cycloalkanes, and aromatics (including polyaromatic hydrocarbons). All spectra were dominated by the ion series C n H Ć¾ 2nĆ¾1 (m/z 29, 43, 57, 71, 85,y), which is typical of saturated normal and branched alkanes.…”
Section: Article In Presssupporting
confidence: 90%
“…The diesel exhaust spectrum was compared to laboratory generated diesel fuel and lubricating oil spectra and the study concluded that under most operating conditions the organic carbon fraction of in-use diesel vehicle exhaust aerosol is dominated by the recondensed vapour from the evaporated engine lubricating oil. These findings were similar to those found by Tobias et al (2001), which concluded that the dominant organic components of fuel and lubricating oil are n-alkanes, branched alkanes, cycloalkanes, and aromatics (including polyaromatic hydrocarbons). All spectra were dominated by the ion series C n H Ć¾ 2nĆ¾1 (m/z 29, 43, 57, 71, 85,y), which is typical of saturated normal and branched alkanes.…”
Section: Article In Presssupporting
confidence: 90%
“…Indeed, lower UFP exposures were expected at increased wind speeds owing to the dispersion of vehicular emissions, and the observed inverse correlation between ambient temperature and UFP exposures was not surprising as the formation of UFPs from traffic exhaust depends in part on vapor condensation (Korhonen et al, 2004;Kulmala et al, 2004) which is favored at lower temperatures. Specifically, some evidence suggests that organic compounds from unburned fuel and lubricating oil are involved in the formation of UFPs from vehicle exhaust (Tobias et al, 2001;Sakurai et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The precise value of Ļƒ nuc is unimportant and could just as well be set to unity since the majority of particles in the nucleation mode will have aerodynamic sizes below the lowest impactor stage. The density can be adjusted lower in the event that the nucleation mode is predominantly hydrocarbon in origin, as with heavy duty diesel engines (Tobias et al 2001), or higher in the case of high sulfate content, as suspected for light duty diesels (Scheer et al 2005).…”
Section: Extension To Bimodal Distributionsmentioning
confidence: 99%